English Language Students’ Perception of Their Preparedness in Doing Online Teaching - Dhamma, Satya; Triprihatmini, Veronica (Universitas Muria Kudus, 2024)
The COVID-19 pandemic in 2020 made students and teachers teach and learn from home. The teaching and learning experience changed to an online environment. This research was intended to explore the English Language Education Study Program (ELESP) students’ preparedness doing online teaching and their challenges in doing so.This research employed the mixed method strategy. The instruments were questionnaires and interviews. The participants were 68 ELESP students from batch 2017 in Sanata Dharma University. There were 4 participants involved in the interview.The findings of this research showed that the ELESP students perceived that they were prepared to do online teaching. The students perceived that the lessons they got in their study program were adequate to prepare themselves to conduct online teaching. However, the students were faced with some challenges in preparing for online teaching. This research concluded that technical problems, difficulties in creating a supportive environment for learning, and adapting to an online environment were the challenges that the ELESP students faced in their experience during the PLP-PP program.Keywords: preparedness, online teaching, pre-service teachers.